Impact Of A Recreational Approach To Improve Shooting Accuracy Among Basketball Players - Hamed Ali Abdulhussein (Journal Sport Science Indonesia, 2026)
This research aims to identify effect of a recreational program on improving shooting accuracy among basketball players. The researcher used experimental method using a single-group pre- and post-test design, as it is suitable for nature of research and its objectives. Sample was chosen randomly from basketball players, and main sample consisted of 12 players, in addition to a pilot sample used to conduct scientific procedures for tests used, consisting of 12 players, to achieve research objectives, the researcher designed a recreational program that included a set of games and recreational activities related to shooting skills in basketball, and it was implemented for 8 weeks at a rate of 3 units per week, and duration of unit was 60 minutes. The researcher used a set of shooting accuracy tests, which included free throw test, ladder shot test, stationary shot test, jump shot test, and test of shooting from several positions around the basket. Results showed statistically significant differences between pre- and post-measurements of experimental group in favor of post-measurement in all shooting accuracy tests under investigation, which indicates effectiveness of recreational program in improving shooting accuracy of basketball players. The researcher recommended necessity of employing recreational programs within training programs for basketball players, benefiting from competitive recreational activities in developing various basic skills, and conducting more similar studies on different age groups and skill levels.